Parascapular Flap for Severe Hidradenitis Suppurativa - Saad Khayat; Nuria Bonsfills; Raúl Antúnez-Conde; Sara Álvarez-Mokthari; Hubert Aranibar; Manuel Tousidonis; Mario Fernández-Fernández; Alberto Díez-Montiel (Karger Publishers, 2024)
Hidradenitis suppurativa is a chronic inflammatory disease which affects apocrine glands and hair follicles of the skin, primarily in the axillary and groin regions. This condition can be highly debilitating, causing painful lesions and a negative psychological impact on patients. While medical and minimally invasive treatments are available, surgical intervention may be necessary for severe cases. In cases involving axillary defects, the use of local flaps such as the parascapular flap is a viable option. In this case report, we present a 34-year-old woman who presented to our clinic with a history of recurrent abscesses and cutaneous infections in the axillary region. After thorough evaluation, we chose to use the parascapular flap for reconstruction. The parascapular flap is a one-stage procedure that allows for extensive resection of the axillary area without resulting in contractions or retractions over the long term. Additionally, this technique allows for preservation of the axilla's original shape with minimal donor site morbidity.